Intra-Industry Trade Between Malaysia and Selected ASEAN Countries - Daud, Adrian (2002)
This study analyses the intra-industry trade (IIT) in selected manufacturing sector, the SITC 7 classification under the Standard International Trade Classification (SITC) between Malaysia and four ASEAN countries (Indonesia, Philippines, Singapore, and Thailand). The share of SITC 7 in Malaysia's exports today is more than 40% and we seek to measure the level of IIT between Malaysia and those ASEAN countries from 1970 to 2000. At the same time, we are interested in analysing the volume, growth, and flow of trade among these countries. Some product groups (728, 759, 764, and 776) within the SITC 7 that contributed significantly within this classification in trade since 1 980 are analysed. 1he method of analysis involves calculating the G-L index; the volume of trade in terms of total trade (IT), intra-industry trade (IIT), and net trade (NT); changes in the volume of trade; and the graphical illustration of trade composition by using the industry trade box (ITB). It is found that the level of IIT was very low for the case of Indonesia and the Philippines during the 1970s and slowly increased in the 1980s. The level of IIT was already high for Singapore and Thailand in the 1970s, but decreased for Singapore in the 1990s and slightly decreased for Thailand in the late 19808. Thailand has replaced Singapore as the country with the highest IIT level with Malaysia in the 1990s. Trade in the selected product groups shows that Malaysia traded heavily with Singapore in all of the groups and then followed by Thailand in most of the groups. Thailand shows more flows in both directions in all of the groups and although this happened in the other groups with the other countries, the norm is that goods flow mostly in one direction. In the 1980s IIT level was low for Indonesia and Philippines but high for Singapore and Thailand. lIT level in 19908 decreased for Singapore in all groups but increased for Thailand in all groups, except product 728. So it can be concluded that Singapore and Thailand have been the more active IIT partner with Malaysia. Although time series analysis on IlT is rare, the influence of income (PCI) and country size (GOP) on IIT is analysed in this study and it is found that PCI has a positive influence on IIT. GOP also affect IIT positively for Indonesia and Philippines, but negatively for Singapore and Thailand. Thus this simple model gives us a consistent result for PCI but not for GDP. This is because IIT level for Singapore decreased in the 1990s and the decrease in IIT for Thailand during the second half of the 1980s.